Economic rents and the contours of conflict in the data-driven economy - Dan Ciuriak (Centre for International Governance Innovation (CIGI), 2020)
In the era of continuous and steadily accelerating technological change that started with the Industrial Revolution, economies and societies were repeatedly transformed in ways that can be traced to ownership of the essential and scarce factor of production of the day and command of the economic rents that flowed to that factor. The digital transformation is now ushering in a new economic era, in which the economy is again being reordered by new technologies based on a new essential capital asset - data. Data generates massive rents, fuels the rise of superstar firms and generates powerful incentives for strategic trade and investment policy. The emergence of this new economy signals a new era of conflict, on new battlegrounds and with new tools or weapons, between new coalitions within and between countries. This paper describes the contours of the conflicts that are to be expected with the digital transformation as it realigns interests; compares these expectations with actual developments; and comments on the strategies of the main protagonists and the implications for the rules-based system of international commerce.
Keywords: 330; Digitalization; New Economy; Political Conflict; Digitalisierung; New Economy; Politischer Konflikt